Sex and Rate Change Differences in QT/RR Hysteresis in Healthy Subjects - Andršová, Irena; Hnatkova, Katerina; Šišáková, Martina; Toman, Ondřej; Smetana, Peter; Huster, Katharina M.; Barthel, Petra; Novotný, Tomáš; Schmidt, Georg; Malik, Marek (Frontiers in Physiology, 2022)
While it is now well understood that the extent of the QT interval changes due to underlying heart rate differences (i.e., the QT/RR adaptation) needs to be distinguished from the speed with which the QT interval reacts to heart rate changes (i.e., the so-called QT/RR hysteresis), gaps still exist in the physiologic understanding of the QT/RR hysteresis processes. The present study was designed to address the questions whether the speed of QT adaptation to heart rate changes is driven by time or by the number of cardiac cycles; whether the QT interval adaptation speed is the same when heart rate accelerates and decelerates; and whether the characteristics of QT/RR hysteresis are related to age and sex. The study evaluated 897,570 measurements of QT intervals together with their 5-minute histories of preceding RR intervals, all made in 751 healthy volunteers (336 females) aged 34.3±9.5 years. Three different QT/RR adaptation models were combined with exponential decay models that distinguished time-based and interval-based basis of QT/RR hysteresis. In each subject and for each modelling combination, best-fit combination of modelling parameters was obtained by seeking minimal modelling residuals. The results showed that the response of QT/RR hysteresis appears to be driven by absolute time rather than by the numbers of cardiac cycles. The speed of the QT/RR hysteresis was found decreasing with increasing age whilst the duration of individually rate corrected QTc interval was found increasing with increasing age. Contrary to the longer QTc intervals, the QT/RR hysteresis speed was faster in females. The QT/RR hysteresis differences between heart rate acceleration and deceleration were not found physiologically systematic (i.e., they differ between different healthy subjects) but on average, the QT/RR hysteresis speed was found slower after heart rate acceleration than after rate deceleration.